KEY SUCCESS OF PROPERTY DEVELOPMENT IN NORTHEAST THAILAND: KHON KAEN AND UDON THANI - Wongjinda, Nipon; Tungbenchasilikul, Sahanon (PEOPLE: International Journal of Social Sciences, 2018)
The research aimed to explore the property market and study the readiness of the property business development in northeast Thailand. The first part was concerned with price determination analysis of the market with the use of multiple regression analysis in Khon Kaen and Udon Thani. Results showed that the factors had the positive impact on property price are the size or usable area, number of bedrooms, size of garden, parking lot, fitness & swimming pool and the security system. While the negatively influenced factors were the promotion, marketing policy and distance of community. The second part examined both producers’ and government’s decision making in the property development with the adoption of logistic regression analysis. Empirical results indicated that the readiness of the property development in northeastern Thailand was 96%, while, Khon Kaen readiness was 85.03% and Udon Thani readiness was 93.75% respectively. The influential factors included city planning system, the higher per capita income, being near the super store, the credit policy and environmental impact analysis.